The opinions and feelings about their educational needs and role of familial caregivers of Parkinson’s Disease patients: a qualitative study - Cianfrocca, Claudia; Caponnetto, Valeria; Donati, Daniele; Di Stasio, Enrico; Tartaglini, Daniela; Lancia, Loreto (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work. In the advanced stages of Parkinson’s Disease, patients need complex care and support, especially at home, where they often receive assistance by familial caregivers. However, caregivers may be or feel unable to cope with their role and, despite the needs of caregivers are often assessed in the literature, their opinions and feelings about these needs are not widely explored yet. This study aimed at exploring the opinions and feelings about their educational needs and role of familial caregivers of Parkinson’s Disease patients. Methods. A qualitative study was conducted from October to December 2017 in a polyclinic of central Italy. Fourteen caregivers voluntarily participated in the study; semi-structured face-to-face interviews were conducted, and audio recorded until data saturation. Two investigators reviewed the transcribed notes, created Meaning Units, Sub-categories and finally the Categories with emerged themes. Results. The analysis of the 14 interviews generated three categories: supportiveness of healthcare educational programs; sense of inability to manage caregiver tasks; need for interaction with other familial caregivers. Conclusions. The caregivers declared their belief that healthcare educational courses can be useful in helping them live and understand the caregiving tasks and expressed their need to share their experiences with other caregivers. In fact, they often they felt abandoned and poorly trained for the patient’s management at the home. The clinical practice should allow healthcare professionals to meet the training and emotional needs of caregivers and create a trust relationship with them to make caregivers skilled in caring for patients.